Allergy Modulation: Exploring the Role of Prebiotics, Probiotics, and Synbiotics in Enhancing Health Outcomes - A Literature Review - Karoń, Łukasz Mikołaj; Zygmunt, Anna; Karoń, Karolina; Grabowski, Wojciech; Pedrycz, Daria; Pedrycz, Emilia; Drapała, Grzegorz (Quality in Sport, 2024)
This literature review explores the role of prebiotics, probiotics, and synbiotics in the prevention and management of allergic diseases, including eczema, asthma, allergic rhinitis, and food allergies. The review delves into the mechanisms by which these dietary interventions modulate the gut microbiome, influence immune system responses, and enhance the epithelial barrier. While prebiotics promote the growth of beneficial gut bacteria and the production of short-chain fatty acids, probiotics introduce live microorganisms that restore balance in the gut ecosystem. Synbiotics combine both approaches to synergistically improve gut health. Despite the promising potential of these interventions, the evidence remains mixed, with their efficacy varying across different allergic conditions. This review underscores the need for further research to clarify the effectiveness of prebiotics, probiotics, and synbiotics in allergy prevention and management, highlighting the complexities involved in translating these findings into clinical practice.